The Development of Local-Based Teaching Materials Using Inquiry Learning in Class IV of 105346 Public Elementary Schools Araskabu, School Year of 2019/2020 - Khairunnisa Putri; Phil. Ichwan Azhari; R. Musrid (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Nowadays when looking at the behavior of students in the learning process at school, it is known that a student learns because it is an obligation not a necessity. As a result, students do not understand the learning material delivered by the teacher. For this reason, a teacher is required to find the main problem of these problems so that the right solution can be found. This research is a research development (Research and Development). This development research was carried out to produce learning tools which would then be tested in class. Learning tools developed are learning tools with local-based teaching materials in Inquiry Learning. The results of observations through observation and interviews with teachers and students of Class IVSD Negeri 105346 Araskabu in the field showed that teaching and learning activities were almost completely dominated by teachers using conventional methods, namely lectures, notes and assignments. Activities carried out by students during the learning process include sitting neatly, listening to the teacher teach, taking notes, and doing questions. There are also many students who chat and enjoy their respective activities during the learning process. Most elementary school teachers consider themselves to be the introduction of knowledge. When teachers carry out the teaching and learning process in the classroom, learning activity is rarely found that involves students being actively involved, such as discussing, making discoveries, or testing a concept or theory using one of the learning approaches. Such learning will cause negative reactions for students, such as: (1) Students look lethargic, not enthusiastic and even sleepy; (2) Students find learning boring; (3) The results of learning are not in accordance with what is stated in the learning objectives. The negative reactions above lead to low student understanding because the methods used by the teacher are not in accordance with the characteristics of the students being faced.